Elemento(III) Derivatives of N-(2-Hydroxy-3-Methyl Benzyl) Valine - P. Pande, Ashutosh; Kandpal, Manju; Shah, Ranjana; B. Mishra, Shasti; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Elemento(III) viz, boron, aluminium, iron, arsenic and antimony derivatives of N-(2-hydroxy-3-methyl benzyl) valine have been prepared by the interaction of their corresponding isopropoxides with the latter, in appropriate stoichiometry in benzene medium.